Health risk assessment of heavy metals (lead and cadmium) in transgenic corn in Tehran - Soha Hatami; Zahra Mousavi; Parisa Ziarati (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2022)
Corn plant and the products made from corn is one of the major transgenic concerning in the world, and due to public concerns about the presence of heavy metals in this product; the present study investigated the food safety in transgenic corn samples due to the presence of lead and cadmium. Iran has the highest exchange of agricultural products. Five packaged popular brands of raw corn samples and one unpackaged one as the bulk sample were purchased from Tehran markets in 2021, and after confirming transgenicity by quantitative real-time PCR and then wet digestion method. The heavy metal contents in all studied samples were analyzed by inductively coupled plasma spectrometer. Bulk samples had the highest content of lead and cadmium compared to other packaged studied samples. The comparison of lead and cadmium compared to the maximum permissible levels set by the National and international standards revealed that the these toxic heavy metals ‘contents in 100% of studied raw corn samples were higher than the maximum limit. The results of current study indicate that the Lead and Cadmium contents in the studied samples were 18 and 2.7 times higher than the maximum permissible limit (MPL).